STUDENTS’ INVESTMENT INTEREST IN STOCK MUTUAL FUNDS - Gatra Gumelar Hadi (Jurnal Ilmiah Mahasiswa FEB, 2019)
The objective of this research is to analyze the effect of attitude, subjective norms, and perceived behavioral control on the interest of students of the Faculty of Economics and Business of Universitas Brawijaya to invest in stock mutual funds. The data of this study harvested through a survey on 344 respondents, who were selected using snowball sampling. Logistic regression was used as an analysis and hyphotesis significantly influence students’ interest to invest in stock mutual funds and that attitude does not affect the said interest.Keywords: Investment, stock mutual funds, subjective norm, perceived behavioral control, logistic regression, theory of planned behavior